Strategi Pemasaran Industry Kreatif Pada Program MBKM Kewirausahaan Rajutan: Studi Kasus Bisnis Rajutan Be Bloomy Bouquets - Siti Saniati Saparina; Firda Isnawati; Hilmi Satria Himawan; Wehdawati Wehdawati; Sofyan Hakim (Pusat Riset dan Inovasi Nasional, 2026)
This community engagement program addresses the limited digital marketing utilization of Be Bloomy Bouquets, a creative knitting business, within the MBKM Entrepreneurship framework. The program aims to design and implement adaptive digital marketing strategies to enhance brand visibility, competitiveness, and business sustainability. Using a Participatory Action Research (PAR) approach, the program was conducted from October to November 2025 through preparation, implementation, and evaluation stages. The results indicate that digital marketing assistance via Instagram and TikTok significantly increased audience reach, customer interaction, and brand awareness, while marketplace utilization still requires further optimization. The discussion highlights that integrating handmade product creativity, digital branding strategies, and participatory reflection fosters entrepreneurial behavior change and strengthens local leadership capacity. In conclusion, the program generates not only technical improvements in marketing performance but also social transformation through enhanced digital literacy, independence, and local leadership. Future recommendations emphasize content consistency, production management, and sustainable digital marketing strategies.